2021
DOI: 10.1177/23259671211032543
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gene Expression of Inflammation- and Fibrosis-Related Factors Between the Anterior and Posterior Capsule in Patients With Rotator Cuff Tear and Shoulder Stiffness

Abstract: Background: Arthroscopic capsular release is an effective treatment for refractory shoulder stiffness, yet there are no basic studies that can explain the extent of the release. Purpose: This study aimed to compare the genetic expression of inflammation- and fibrosis-related factors between the anterior and posterior capsules in patients with shoulder stiffness and rotator cuff tear. Study Design: Descriptive laboratory study. Methods: Enrolled in this study were 35 patients who underwent arthroscopic capsular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Rotator cuff tear (RCT) is another common glenohumeral complaint inducing joint pain and dysfunction especially in elderly [4]. In patients with RCT, the portion of concomitant adhesive capsulitis can be 10% to 40% [5,6], while in patients with adhesive capsulitis, ~ 30% have concomitant full-thickness RCT [7]. Surgically repairing of the torn rotator cuff has been accepted worldwide for decades, yielding overall satisfactory results [8], but how to treat RCT in patients with adhesive capsulitis is still controversial.…”
mentioning
confidence: 99%
“…Rotator cuff tear (RCT) is another common glenohumeral complaint inducing joint pain and dysfunction especially in elderly [4]. In patients with RCT, the portion of concomitant adhesive capsulitis can be 10% to 40% [5,6], while in patients with adhesive capsulitis, ~ 30% have concomitant full-thickness RCT [7]. Surgically repairing of the torn rotator cuff has been accepted worldwide for decades, yielding overall satisfactory results [8], but how to treat RCT in patients with adhesive capsulitis is still controversial.…”
mentioning
confidence: 99%
“…They reported that more fibrous processes occur in the anterior capsule than in the posterior capsule in patients with stiffness. 12 The levels of fibronectin, matrix metalloproteinase-2, and matrix metalloproteinase-9 in the anterior capsule were significantly higher than those in the posterior capsule. 12 These pathophysiological and histological results also support our findings on the significance of anterior capsular thickness.…”
Section: Discussionmentioning
confidence: 84%
“… 24 Moreover, anterior capsular thickening was frequently evident on arthroscopy in patients with stiffness. 30 , 31 Similarly, Kim et al 12 conducted a prospective study to compare the genetic expressions of inflammation- and fibrosis-related factors in the anterior and posterior capsules between patients with and without stiffness and having RCT. They reported that more fibrous processes occur in the anterior capsule than in the posterior capsule in patients with stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it may impede post‐operative rehabilitation after rotator cuff repair and reduce the quality of life [6, 15, 33, 44]. The stiffness arises from post‐surgical adhesion in the subacromial space and capsular contracture [30, 45]. The procedures performed, such as acromioplasty, bursectomy, or footprint preparation, may cause bleeding, contributing to fibroblast proliferation and the progression of fibrous scar tissue adhesion [30, 50].…”
Section: Introductionmentioning
confidence: 99%
“…The stiffness arises from post‐surgical adhesion in the subacromial space and capsular contracture [30, 45]. The procedures performed, such as acromioplasty, bursectomy, or footprint preparation, may cause bleeding, contributing to fibroblast proliferation and the progression of fibrous scar tissue adhesion [30, 50]. To overcome post‐operative shoulder stiffness, meticulous hemostasis and capsular release should be performed, especially for patients with preoperative stiffness, intraarticular steroid injection, or early post‐operative rehabilitation [7, 8, 22, 27, 29].…”
Section: Introductionmentioning
confidence: 99%